Beyond equilibrium: revisiting two-sided markets from an agent-based modelling perspective. (3rd June 2019) - Heinrich, Torsten; Gräbner, Claudius
Two-sided markets are an important aspect of today's economies. Yet, the attention they have received in economic theory is limited, mainly due to methodological constraints of conventional approaches: Two-sided markets often exhibit non-trivial dynamics that are difficult to describe via analytical equilibrium models. We illustrate this point by revisiting a well-known equilibrium model of two-sided markets by Rochet and Tirole from an agent-based computational perspective. We identify several inconsistencies as well as implicit and implausible assumptions of the original model. These limit its explanatory power and motivate an alternative approach. The agent-based model we propose allows us to study two-sided markets in a more realistic and adequate manner: Not only are we able to compare different decision-making rules for the providers, we can also study situations with more than two providers. Thus, our model represents a first step towards a more realistic and policy-relevant study of two-sided markets.